P5RA DENGAN TEMA BANGUNLAH JIWA DAN RAGANYA CEGAH KASUS PERUNDUNGAN VERBAL DI LINGKUNGAN SEKOLAH - Erna Sari Agusta; Yasmiarti (Jurnal Lingkar Mutu Pendidikan, 2025)
Cases of bullying in schools continue to increase, some of which even end in very detrimental actions such as physical violence, trauma, or decreased academic achievement. Cases of bullying can occur due to a lack of knowledge about bullying itself. To create schools that are safe from bullying, education is needed, both in the form of learning and anti-bullying projects. The aim of this research is to determine the impact of the P5RA project with the theme Build Your Body and Soul on cases of verbal bullying in schools. This research was conducted on 194 grade 7 students at MTsN 28 Jakarta. This research uses qualitative methods. The data collection technique in this research was carried out in 3 stages, namely the identification stage, follow-up efforts, and monitoring the results of activities. The data collection instruments used by researchers in this research were tests, questionnaires, interviews and documentation. The results of the research showed an increase in the percentage of each indicator of the bullying understanding test to more than 75%. Apart from that, there was a decrease in the percentage of students who were bullies, experienced verbal bullying, bullied in class, and an increase in the percentage of students who felt safe at school, had an empathetic attitude, rejected bullying, and reported cases of bullying. Thus, it can be said that the P5RA project with the theme Build Your Body and Soul can overcome and prevent cases of bullying in schools.